Long-term functional and anatomical evolution in surgically closed macular holes with internal limiting membrane peeling. Issue 5 (September 2020) - Eymard, Pauline; Le Mer, Yannick
Introduction: The aim of this study was to describe the long-term evolution of macular retinal thickness and visual acuity in patients who present surgically closed full-thickness macular hole, operated by vitrectomy with internal limiting membrane peeling. Methods: A retrospective observational study of patients operated for full-thickness macular hole with closure of the hole and at least 6 months of post-operative follow-up was performed. All patients had pars plana vitrectomy, peeling of the internal limiting membrane, gas filling and positioning. Comparison of the early post-operative (in the first 5 months) visual acuity and spectral-domain optical coherence tomography-measured macular thickness with late post-operative data (between 6 months and 6 years) was performed. Foveal retinal thickness and temporal and nasal retinal thickness between 1 and 3 mm from the centre were recorded. Results: In total, 35 eyes of 34 patients were included, with an early post-operative measure realized at a mean of 1.8 months and a late measure done at a mean of 25.5 months (7–73 months). Foveal thickness stayed unchanged (282 vs 288 µm), nasal parafoveal thickness remained increased compared to normal and stayed constant (345 vs 345 µm) and temporal parafoveal macular thickness was decreased (313 vs 308 µm) ( p  = 0.028). Best-corrected visual acuity was improved by the surgery and the gain increased over time. Conclusion: Internal limiting membrane peeling improves anatomical success of full-thickness macular hole, but this procedure is not without long-term scalable consequences on macular thickness on the temporal quadrant (thinning) as on the nasal quadrant (thickening).